Hydrocarbon source-rock potential of the Jurassic succession in eastern part of the North Western Desert, Egypt - Mostafa M. Lotfy; Esam A. Abd El Gawad; Abdalla Abdelghafar (Egyptian Journal of Petroleum)
The hydrocarbon potential is determined by the quantity and quality of organic matter encountered in the Jurassic sediments in two wells at the Northern Western Desert. It utilizes to define the zones of oil and gas using the well logging data for calculates the total organic carbon (TOC). The evaluation of source rock has been based on two steps; the first one depended on the geochemical parameters including TOC, S1, S2, Tmax, and Vitrinite reflectance (Ro %) of two wells JG-1 and JD-4. The second step was to calculate (TOC) from wireline logs. The well log types utilized in such kind of analysis are the density log, sonic log, resistivity log and gamma-ray log. The stratigraphic sequence, in the studied wells ranges in age from Paleozoic to Recent. The present work focuses on the Jurassic rocks represented by Khatatba Formation as they include the main source horizon. Based on the obtained results, Jurassic sediments called as fair to excellent source rock potential. The genetic type of organic matter can be identified through the study of pyrolysis data, which indicate that is rich in mixed oil and gas-prone kerogen except few samples reflect type I organic facies.